Challenges of Nurses Professional Socialization and Solutions - Mousavizadeh, narjes; Ashktorab, Tahereh; Shabani, fatemeh (Advances in Nursing & Midwifery, 2017)
Abstract Background and Aim: Professional socialization is the process of gaining and internalizing knowledge, skills, values, attitudes, beliefs and behaviors of a specific profession. Through the process gradually, a sense of belonging, and unique professional identity will develop. The aim of this study was to review the barriers, conditions and facilitators of nurses’ professional socialization. Materials and Methods: This is a review article. Electronic journals and databases such as CINAHL, Embase, Medline, Scopus, ScienceDirect, MDConsult, OVID, Google Scholar was searched to find studies have been investigated the various aspects of "professional socialization of nurses. Results: The results showed that the work environment and corporate culture, the gaps between theory and practice in nursing and community’s attitude toward nursing profession are effective factors in nurses’ professional socialization. Promote personal and professional capabilities, reform of resources and organizational structure and training structure, are the strategies for improving nurse’s socialization. Conclusion: Among the factors involved in nurses’ socialization, formal education system and teachers can have the greatest impact positively or negatively on the professional growth and development of nurses. Therefore, planning to facilitate and promote the professional socialization of nurses, with emphasis on improving the education system and bridging the gap between theory and practice should be considered. Keywords: Socialization; Nurse; Review